2001
DOI: 10.1136/thorax.56.2.121
|View full text |Cite
|
Sign up to set email alerts
|

Leucocyte response and anti-inflammatory cytokines in community acquired pneumonia

Abstract: Background-In the host defence of the lung neutrophils (PMN) play a central role. Apart from antimicrobial properties, recent data indicate that PMN also exert anti-inflammatory eVects by stimulation and release of cytokine antagonists such as interleukin-1 receptor antagonist (IL-1ra). Methods-Cytokine release from lipopolysaccharide stimulated whole blood was studied in 18 patients with community acquired pneumonia (CAP) and severe co-morbidities at admission and after 24 hours. Release of IL-1ra, interleuki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
32
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 23 publications
6
32
0
1
Order By: Relevance
“…No acute phase response was observed for IL-5, IL-12, IFN-c, MCP and MIP. Our results are comparable with former findings in human and experimental pneumococcal pneumonia, in which the inflammatory response is characterised by an extended pro-inflammatory response resulting in high levels of IL-6 and IL-1RA [2,10,13,21,[35][36][37]. In this study, cytokines and chemokines were only measured in serum.…”
Section: Community-acquired Pneumonia H Endeman Et Alsupporting
confidence: 79%
See 2 more Smart Citations
“…No acute phase response was observed for IL-5, IL-12, IFN-c, MCP and MIP. Our results are comparable with former findings in human and experimental pneumococcal pneumonia, in which the inflammatory response is characterised by an extended pro-inflammatory response resulting in high levels of IL-6 and IL-1RA [2,10,13,21,[35][36][37]. In this study, cytokines and chemokines were only measured in serum.…”
Section: Community-acquired Pneumonia H Endeman Et Alsupporting
confidence: 79%
“…The human immune response to CAP varies between the different causative microorganisms and severities of disease. An important early component of the host response is the release of cytokines produced by inflammatory cells [2,3]. In experimental settings, the appearance of cytokines depends on the time after induction of endotoxaemia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7 17 18 Leucopenia was also associated with an almost fourfold higher risk of any or early treatment failure. In a recent study Kolling et al 19 found that leucocytes had a beneficial effect in CAP, not only due to their antimicrobial activity but also because they are able to modulate the pro-inflammatory cytokine response.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it appears likely that, under inflammatory conditions in the lung, increased levels of several shedding products are found in the alveolar fluid. In fact, this has been described for CX3CL1, JAM-A, CXCL16, TNF, TNFR, TGF-␣, IL6R, and syndecans in human sputum samples (20,89,123,153,198) or murine alveolar lavage fluid (32,33,148).…”
Section: Adam17mentioning
confidence: 99%